How should patients be selected for clinical clerkship cases: should they be young, middle-aged, or older? - Yan Peng; Weiwei Sun; Yu Zhang; Xinliang Zou; Zhouqing Zhang; Tao Jing (Critical Public Health, 2025)
Clinical clerkship learning effectiveness is influenced by patient age, but there has been limited research in this area. This study explores the relationship between patient age and clerkship learning, investigating its impact on learning outcomes. We randomized 30 clerkship students into three groups and categorized them into three groups: young (18–40 years old), middle-aged (41–65 years old), and older (66 years and above). Students conducted consultations and physical examinations with patients from their respective age groups. The assessment included teacher feedback, post-class interview-based questionnaire surveys, and test scores. The study revealed the highest level of student satisfaction was among middle-aged patients, followed by young patients, and the lowest level of satisfaction was among older patients. Classroom interest and consultation participation were similar between young and middle-aged individuals but greater than they were among older individuals. Physical examination ratios were higher in middle-aged and older individuals than in young individuals. Theoretical test scores were consistent across age groups, but practical test scores were higher among middle-aged and older individuals. These results suggested that clinical educators should consider the age of patients and the use of middle-aged patients as learning cases to increase communication and clerkship effectiveness.